Counter-revolution : liberal Europe in retreat - Zielonka, Jan 1955- (Oxford University Press, 2018)
From revolution to counter-revolution -- Why they hate liberals -- Democratic malaise -- Socialism for the rich -- Geopolitics of fear -- Barbarians at the gate -- The rise and fall of the EU -- Peering into the future